Technologies for Type 1 Diabetes and Contact Dermatitis: Therapeutic Tools and Clinical Outcomes in a Cohort of Pediatric Patients - Passanisi, Stefano; Salzano, Giuseppina; Galletta, Francesca; Aramnejad, Sara; Caminiti, Lucia; Pajno, Giovanni B.; Lombardo, Fortunato (Frontiers in Endocrinology, 2022)
The increasing use of technological devices for the management of diabetes is related to the prolonged exposure of patients’ skin to chemical and mechanical agents and, consequently, to the increased risk of developing dermatological complications. Among these, contact dermatitis is the most insidious skin disorder. Despite the magnitude of the issue, no universally accepted recommendations on the management of this common complication are currently available. Our observational study aimed to describe all the solutions adopted by patients and their caregivers to treat and prevent the appearance of contact dermatitis and to describe the clinical impact of this cutaneous complication. Twenty-one pediatric patients (mean age 12.1 ± 3.7 years) with type 1 diabetes were recruited in the study. The most common treatment used to treat acute skin lesions was the application of topical corticosteroids, sometimes associated with topical antibiotics (9.5%). In order to prevent the further appearance of dermatitis, the most frequently adopted measure was the use of hydrocolloid and/or silicone-based adhesives, followed by the application of protective barrier films. One patient reported benefit from the off-label use of fluticasone propionate nasal spray. However, only 52.4% of the study participants achieved a definitive resolution of the skin issue, and 38.1% of patients were forced to discontinue insulin pump therapy and/or continuous glucose monitoring. No differences were observed in glycated hemoglobin values between the period before and after the onset of contact dermatitis. Our study confirms the severity of this dermatological complication that may hinder the spread of new technologies for the management of diabetes. Finally, our findings highlight the importance of establishing close collaboration both with pediatric allergy specialists to prescribe the most suitable treatment and with manufacturing companies to ensure that adhesives of technological devices are free of harmful well-known sensitizers.